MODERN GEOSOCIAL TRENDS IN CENTRAL ASIA (Scientific journal of the Fergana State University, 2026)
This article provides a scholarly analysis of current geopolitical trends unfolding in Central Asia, emphasizing their implications for regional cooperation and stability. The author explores the institutionalization of intergovernmental dialogue among Central Asian countries, focusing on the development of the “C5+” strategic partnership platform as a mechanism to foster long-term integration and regional resilience. The article also examines the increasing activity of global geopolitical actors, the emergence of new regional power dynamics, and the prospects for collaboration with international organizations and leading global powers. The study concludes with a set of evidence-based recommendations and scientific insights.